Inner Armor: Role of Spiritual and Psychological Well-Being on Compassion Fatigue Among Nursing Students - Casirayan, Joe Mari; Cunanan, Gloria (International Journal of Sustainability and Advanced Integrated Research, 2026)
Compassion fatigue is an increasing concern in nursing education because students are exposed to academic demands, clinical responsibilities, patient suffering, trauma, and emotionally difficult care situations while still developing professional competence and coping capacity. This study aimed to determine the role of spiritual well-being and psychological well-being in compassion fatigue among third- and fourth-year nursing students at Capitol University. The study was anchored on Jean Watson’s Theory of Human Caring, Figley’s Compassion Fatigue Theory, and Betty Neuman’s Systems Model, which collectively framed spiritual well-being and psychological well-being as internal protective resources or “inner armor” against emotional exhaustion and trauma-related stress. A quantitative approach using descriptive, correlational, and causal-comparative designs was employed. The respondents were 243 third- and fourth-year nursing students selected through stratified random sampling. Data were gathered using standardized and adapted self-report instruments, including the Spiritual Well-Being Scale for religious and existential well-being, the Connor-Davidson Resilience Scale for psychological resilience, the Mindful Attention Awareness Scale for trait mindfulness, and the Professional Quality of Life Scale Version 5 for burnout and secondary traumatic stress. Data were analyzed using mean, standard deviation, Pearson’s correlation coefficient, and multiple regression analysis. Findings showed that nursing students had high levels of spiritual well-being and psychological well-being, while compassion fatigue was moderately high in terms of burnout and secondary traumatic stress. Religious and existential well-being had significant moderate negative correlations with compassion fatigue, while resilience and trait mindfulness had stronger significant negative correlations. Regression analysis showed that the combined model significantly predicted compassion fatigue, with resilience and trait mindfulness emerging as significant predictors, while religious and existential well-being were not significant predictors when entered simultaneously with the psychological variables. The study concludes that spiritual and psychological well-being function as protective internal resources, with psychological well-being, particularly resilience and mindfulness, playing the strongest role in reducing compassion fatigue. The study recommends strengthening student mental health support, resilience-building, mindfulness training, counseling services, spiritual care, reflective learning, mentoring, and supportive clinical supervision in nursing education and clinical training. The study aligns with SDG 3, Good Health and Well-Being, and SDG 4, Quality Education, because it supports nursing students’ mental health, emotional resilience, and learning readiness. Its sustainability impact lies in promoting institutional, educational, and public health sustainability by helping prepare emotionally stable, compassionate, and resilient future nurses.